THE BEST LITERARY ACHIEVEMENTS OF EASTERN AND WESTERN LITERATURE OF THE XX CENTURY IN THE FIGURE OF RALPH ELLISON - Gulomova, Z. (FAN va JAMIYAT, 2023)
The literature of the ХХ th century occupies an important place in the history of the World. This period did not create an opportunity to realize the true talent of the people of art, to ensure the unity of the language with the soul. Nevertheless, a true people’s writer tried to express the deep desire of his heart through various methods, symbolic images and details. There are such writers in the history of world literature, the significance of their work is revealed more and more with the passage of time. The famous American writer Ralph Ellison is among such writers.